The influence of carbon additive on the electrochemical behaviors of Fe2O3/C electrodes in alkaline solution - Anh, Trinh Tuan; Thang, Doan Ha; Hang, Bui Thi (Vietnam Journal of Science and Technology, 2018)
Acetylene Black (AB) and Fe2O3 nanoparticles were used as the additive and active materials, respectively for preparing Fe2O3/AB composite electrode. The effects of carbon additive and binder content on the electrochemical properties of Fe2O3/AB electrodes in alkaline solution were investigated to find the suitable anode for the Fe/air battery. The results of electrochemical measurements showed that both the AB additive and binder content significantly affected on the electrochemical behaviors of Fe2O3/AB electrodes. AB additive improves in redox reaction of iron oxide.